KUALTTAS BIOLOGI PERAIRAN SUNGAI SENAPELAN, SAGO DAN SAIL DI KOTA PEKANBARU BERDASARKAN BIOINDIKATOR PLANKTON DAN BENTOS - Suwondo '; Elya Febrita; Dessy '; Mahmud Alpusari (Program Studi Pendidikan Biologi, 2004)
Water quality based on plankton and benthic organism as bio-indicators in Senapelan, Sago and Sail Rivers at Pekanbaru city were investigated on April - August 2003. Survey method with purposive random sampling at 7 sampling point was used in the research. Various parameters such as saprobe coefficient indexes, plankton and benthic diversity and also bio-indexes benthic organism were observed Final results had shown that saprobe indexes plankton between - 0,85 until + 1,00. While diversity indexes benthic organism between 0,1 16 - 1,335 and bio-indexes benthic between 1 until 5. Based on the criterion expressed that water quality of biology in Senapelan, Sago and Sail Rivers at Pekanbaru city were middle until heavily polluted. Key words : Biology Quality, Plank tonic, Benthic